(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The globalization concept is regarded one of the modern concept which had seen in the last time while it hadn’t occur now only, but it had seen clearly with the technology &information revolution beside the quick development in the communication net which had made the world like a small village . Since accounting is regarded business language based on integrated theoretical framework consists of many connected objective & rules which led to consistent accounting standards . So with this development there is a clear need to consolidate the concepts , policies ,and applications which the companies use it in treating its financial events .